Feasibility of a standard cognitive assessment in European academic memory clinics - Grazia, Alice; Altomare, Daniele; Preis, Lukas; Monsch, Andreas U.; Cappa, Stefano F.; Gauthier, Serge; Frölich, Lutz; Winblad, Bengt; Welsh-Bohmer, Kathleen A.; Teipel, Stefan J.; Boccardi, Marina (Alzheimer's and dementia, 2023)
Abstract Introduction Standardized cognitive assessment would enhance diagnostic reliability across memory clinics. An expert consensus adapted the Uniform Dataset (UDS)-3 for European centers, the clinician's UDS (cUDS). This study assessed its implementation acceptability and feasibility. Methods We developed a survey investigating barriers, facilitators, and willingness to implement the cUDS. With a mixed-methods design, we analyzed data from academic memory clinics. Results Seventy-eight percent of responding clinicians were experienced neuropsychologists/psychologists and 22% were medical specialists coming from 18 European countries. Sixty-five percent clinicians were willing to implement cUDS. General barriers related to implementation (43%) and clinical-methodological domains (21%). Favorable clinicians reported finances (15%) and digitalization (9%) as facilitating, but unavailability of local norms (23%) as hindering. Unfavorable clinicians reported logistical (23%) and time issues (18%). Discussion Despite challenges, data showed moderate clinicians' acceptability and requirements to improve feasibility. Nonetheless, these results come from academic clinicians. The next steps will require feasibility evaluation in non-academic contexts.
Erstmals veröffentlicht: 01. Dezember 2022
Gesehen am 04.06.2024